(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
This study examines the changes in wetlands in the fringe area of Dhaka city using geospatial assessment techniques. The wetland in the area is crucial as they serve as a buffer zone for the Dhaka Metropolitan Area (DMA) and play a significant role in maintaining the region’s ecological balance. Thirty-meter NASA Landsat 4-5TM and Landsat 8 OLI satellite imagery were used to extract wetland features in the fringe area of Dhaka city. The Modified Normalized Difference Water Index (MNDWI) was applied to delineate wetland features. Finally, ArcGIS geometric computing was used to detect yearly changes, and a Cellular Automaton (CA) Markov Model was applied to predict future transitions. The research findings reveal that wetlands in the Dhaka Metropolitan Area are declining at a rate of 1.1% between 1991 and 2016, indicating the urgency of addressing this issue to ensure the sustainability of the region’s natural resources. The percentage of wetlands in the fringe area has been decreasing significantly over the years, with wetlands making up only 12.98% of the fringe area in 2022, down from 28.22% in 1989. This trend is predicted to continue, with wetlands accounting for only 8.02% of the total area by 2034. The strong negative correlation coefficient between the year and wetland area suggests that the trend of decreasing wetland is likely to continue unless significant measures are taken to protect wetlands. The study highlights the importance of conserving and restoring wetlands in Dhaka’s fringe areas to maintain the ecological balance of the region and support the well-being of both humans and wildlife. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 12(2), 2023, P 97-117